Kelayakan dan Praktikalitas Media Pembelajaran Thunkable Berbasis Android pada Materi Ketahanan Pangan Industri dan Energi Kelas XI IIS SMAN 1 Painan - Heru Kartika Sandra; Momon Dt. Tanamir; Nila Afryansih (Horizon, 2022)
This study aims to determine and analyze the feasibility and practicality of Android-based thunkable learning media on industrial food security and energy materials for class XI IIS SMAN 1 Painan. The type of research used in this research is research and development (Research and Development). With a 4D model that includes 4 stages, namely: Define, Design, Development, Desiminate. The subjects in this study were students of class XI IIS as many as 64 students. The results of the study found that: 1.)Thunkable learning media based on Android is declared very feasible after analyzing data processing using Microsoft Excel so that the total score is 277 with a mean level of 4.85 and a percentage rate of 97% with “Very Eligible” category. 2.) Thunkable learning media based on Android is declared practical after processing the research data obtained from the questionnaire, and a practical test is carried out so that a total score of 2.204 is obtained with a mean level of 4.45 and a percentage of 89% in the "Very Practical" category.  Keywords: Appropriateness, Practicality, Android.